2014
DOI: 10.1007/s00405-014-3175-3
|View full text |Cite
|
Sign up to set email alerts
|

Low bone mineral density and vitamin D deficiency in patients with benign positional paroxysmal vertigo

Abstract: Several studies indicated the association between benign paroxysmal positional vertigo (BPPV) with osteoporosis and vitamin D deficiency implying that abnormal calcium metabolism may underlie BPPV. The aim of the present study is to confirm the correlation between BPPV and both decrease in bone mineral density (BMD) and vitamin D deficiency. The study group included 80 patients with idiopathic BPPV (52 females, 28 males), with age range 31-71 years (47.6 ± 9.1). The patients were divided into two groups; recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
96
4
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(107 citation statements)
references
References 18 publications
3
96
4
4
Order By: Relevance
“…Human otoconia are the sensory detector organs found in the utriculus and sacculus for the detection of linear acceleration and head tilt movements against gravity. They contain more than 90% calcite (crystalized calcium carbonate), and they are the only calcite-based biological structures acting in physiological processes in human beings, whereas other two systems, bone and teeth, contain calcium phosphate [12,13] . Calcium and carbonate levels in the endolymph are critical for normal otoconial function, which is primarily provided by a calcium channel transport system expressed in the inner ear [14] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human otoconia are the sensory detector organs found in the utriculus and sacculus for the detection of linear acceleration and head tilt movements against gravity. They contain more than 90% calcite (crystalized calcium carbonate), and they are the only calcite-based biological structures acting in physiological processes in human beings, whereas other two systems, bone and teeth, contain calcium phosphate [12,13] . Calcium and carbonate levels in the endolymph are critical for normal otoconial function, which is primarily provided by a calcium channel transport system expressed in the inner ear [14] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the ultrastructural and animal studies, clinical studies have also investigated the probable relationship between BPPV and calcium metabolism. Talaat et al [13] demonstrated that BPPV may be associated with low bone mineral density and vitamin D deficiency. Calcium metabolism and oxidative stress are closely linked.…”
Section: Discussionmentioning
confidence: 99%
“…In 2003, Vibert et al [4] observed that osteoporosis, osteopenia, and disorders of calcium metabolism presented more often in female BPPV patients Association of Benign Paroxysmal Positional Vertigo with Osteoporosis and Vitamin D Deficiency: A Case Controlled Study over 50 years of age and concluded that osteopenia and osteoporosis could be potential etiological factors in BPPV. In consequent years, studies conducted in several regions reported a prevalence of osteoporosis and vitamin D (vit D) deficiency in BPPV patients [3,[14][15][16][17] . However, these studies all had major selection bias in that the control group did not represent the population [3,6,14,15] .…”
Section: Introductionmentioning
confidence: 99%
“…In consequent years, studies conducted in several regions reported a prevalence of osteoporosis and vitamin D (vit D) deficiency in BPPV patients [3,[14][15][16][17] . However, these studies all had major selection bias in that the control group did not represent the population [3,6,14,15] . Bone mineral density (BMD) and serum 25-hydroxy vitamin D (25-OH vit D) levels might be affected by various factors such as age, hormonal factors, sex, nutrition and lifestyle habits, and pre-existing metabolic disorders [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…Calcium and vitamin D metabolism is usually affected in pregnancy, especially in the late trimesters due to the rapid growth of the fetus. This may be another risk factor for pregnant women suffering from BPPV (13). However, according to the guidelines of American College of Obstetricians and Gynecologists, vitamin D supplementation should only be recommended to pregnant women at an increased risk (14).…”
Section: Discussionmentioning
confidence: 99%